2020
DOI: 10.1121/10.0002871
|View full text |Cite
|
Sign up to set email alerts
|

Cross-linguistic filled pause realization: The acoustics of uh and um in native Dutch and non-native English

Abstract: It has been claimed that filled pauses are transferred from the first (L1) into the second language (L2), suggesting that they are not directly learned by L2 speakers. This would make them usable for cross-linguistic forensic speaker comparisons. However, under the alternative hypothesis that vowels in the L2 are learnable, L2 speakers adapt their pronunciation. This study investigated whether individuals remain consistent in their filled pause realization across languages, by comparing filled pauses (uh, um) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 30 publications
(87 reference statements)
1
9
0
Order By: Relevance
“…Clark and Fox Tree (2002) found no systematic differences in numbers of occurrences in monologues relative to dialogues (p. 93, Table 2). In addition, we see no reason to assume that the acoustic realization of filled pauses will differ by discourse type, although their position in an utterance is likely to affect their acoustics (Swerts, 1998;de Boer and Heeren, 2020).…”
Section: Recordingsmentioning
confidence: 91%
See 2 more Smart Citations
“…Clark and Fox Tree (2002) found no systematic differences in numbers of occurrences in monologues relative to dialogues (p. 93, Table 2). In addition, we see no reason to assume that the acoustic realization of filled pauses will differ by discourse type, although their position in an utterance is likely to affect their acoustics (Swerts, 1998;de Boer and Heeren, 2020).…”
Section: Recordingsmentioning
confidence: 91%
“…This assumption has been tested in prior work (de Boer and Heeren, 2020) among 58 speakers (a subset of whom is used in the current paper) speaking in their first language (L1) Dutch and second language (L2) English. A control experiment presented in this study showed that these languages both have uh and um with a vowel described as schwa, but it is realized with a 30-40-Hz higher first formant (F1), i.e., more open, by L1 English speakers than L1 Dutch speakers (see de Boer and Heeren, 2020). The sequential bilinguals from our dataset had somewhat higher F1 and lower second formants (F2) in their L2 English-filled pauses than in their L1 Dutch counterparts (de Boer and a) Author to whom correspondence should be addressed, ORCID: 0000-0003-0161-9115. b) ORCID: 0000-0001-7988-1346. c) ORCID: 0000-0001-7124-027X.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…This was produced in the speakers' L1, and if that was not English, also in their L2. L2 speakers are estimated to at least be at the B2 level (see De Boer & Heeren, 2020). For these recordings no fluency judgements were available.…”
Section: Secondary Corpusmentioning
confidence: 99%
“…Two annotators annotated the primary corpora. For the secondary corpus, data from the Dutch L1 speakers, in both languages, had already been annotated by at least two coders (see De Boer & Heeren, 2020). For the English L1 speakers in the secondary corpus, filled pauses were annotated by one coder (3 rd author).…”
Section: Annotations Of the Corporamentioning
confidence: 99%